2011
DOI: 10.1111/j.1460-9592.2011.03702.x
|View full text |Cite
|
Sign up to set email alerts
|

Surgical outcome in children undergoing hypospadias repair under caudal epidural vs penile block

Abstract: Urological Survey 799 Editorial CommentThis study though based on a cross-sectional survey with small patient numbers restraining its power, adds to the limited literature concerning clinically relevant fatigue (CRF) in men with biochemically controlled prostate cancer on long term GnRH-based ADT.The main findings were as follows: -CRF prevalence in the sample was 43% (95% CI 35% to 50%) and the difference in scores between those with and without CRF far exceeded the 20 points described as a 'large' clinically… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
73
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 83 publications
(77 citation statements)
references
References 23 publications
4
73
0
Order By: Relevance
“…In the literature, there are several resarches comparing effective analgesia technique for hypospadias surgery [14,15]. Our experience with hypospadias with or without stent are similar with other same literature researches regarding better results with caudal combined general anesthesia comparing with other modalities like penile block or parenteral analgesia.…”
Section: Discussionsupporting
confidence: 80%
“…In the literature, there are several resarches comparing effective analgesia technique for hypospadias surgery [14,15]. Our experience with hypospadias with or without stent are similar with other same literature researches regarding better results with caudal combined general anesthesia comparing with other modalities like penile block or parenteral analgesia.…”
Section: Discussionsupporting
confidence: 80%
“…Although they were not able to identify how caudal block affected the occurrence of urethrocutaneous fistula, they suggested that penile engorgement after caudal block increases tissue oedema even though there is no direct evidence for this. A previous experimental study has shown that epidural block can increase water content in mesenteric tissue after mesenteric resection and anastomosis in pigs [6], which suggests that caudal blockade might increase postoperative oedema in certain types of tissue, and we agree with Kundra et al that penile engorgement may place the surgical sutures under inappropriate tension, resulting in poor healing [5]. Both postoperative oedema and poor wound healing may contribute to the array of complications after hypospadias repair.…”
Section: Caudal Anesthesia Safety For Hypospadias Repair -A Replysupporting
confidence: 68%
“…However, given that the surgical complication rate after distal hypospadias repair is very low to begin with [4], a larger sample size may be needed in future studies to detect the adverse effects of caudal blockade in this patient population. Kundra et al showed that penile size increased immediately after caudal block in children undergoing hypospadias repair [5], and that all children who suffered from urethrocutaneous fistula had received caudal block. Although they were not able to identify how caudal block affected the occurrence of urethrocutaneous fistula, they suggested that penile engorgement after caudal block increases tissue oedema even though there is no direct evidence for this.…”
Section: Caudal Anesthesia Safety For Hypospadias Repair -A Replymentioning
confidence: 99%
“…Proximal hypospadias is associated with a much higher incidence of all of the complications that were evaluated in this study. When evaluating distal hypospadias alone, the incidence of fistula and all other complications was comparable between the two groups, as noted in the accompanying editorial [2] and found in other papers [3,5]. The abstracts by SotoAviles et al [6], cited in the accompanying editorial in support of an association between caudal analgesia and fistula following hypospadias repair, have yet to be published in a peer-reviewed journal and must be viewed with caution.…”
mentioning
confidence: 65%
“…Kundra et al showed that penile size increased immediately after caudal block in children undergoing hypospadias repair [5], and that all children who suffered from urethrocutaneous fistula had received caudal block. Although they were not able to identify how caudal block affected the occurrence of urethrocutaneous fistula, they suggested that penile engorgement after caudal block increases tissue oedema even though there is no direct evidence for this.…”
Section: B Haydarmentioning
confidence: 99%